Rapid calcination of ferrite Ni0.75Zn0.25Fe2O4 by microwave energy - Assis, R. B.; Bomio, M. R. D.; Nascimento, R. M.; Paskocimas, C. A.; Longo, E. [UNESP]; Motta, F. V. (Springer, 2014)
Ferrites Ni0.75Zn0.25Fe2O4 were obtained by polymeric precursor method and calcined in a short time with microwave energy to assess the morphological and microstructural characteristics. Samples were calcined at 500, 650, 800, and 950 A degrees C for 30 min in a microwave oven. The resulting powders were characterized by thermal analysis (TG/DSC), X-ray diffraction (XRD), Fourier transform infrared spectrometer, field-emission gun scanning electron microscope (FEG-SEM), and energy-dispersive X-ray spectroscopy. The XRD results showed the formation of single ferrite phase at temperature of 500 A degrees C for 30 min. The FEG-SEM analysis showed agglomerated particles with formation of non-dense longitudinal plates, with interparticle porosity and agglomerated fine particles. The rapid calcination by microwave energy demonstrated satisfactory results in relatively low temperature of 500 A degrees C for 30 min and appeared to be a promising technique for obtaining nickel-zinc ferrite powders.
Keywords: Ni-Zn ferrite; Spinel; Polymeric precursors; Rapid calcinations; Microwave